Organizing Pottery Lessons Through Interactive Methods - Ergashev Madaminjon Yuldashevich (Genius Journals, 2025)
Pottery education plays a crucial role in preserving cultural heritage and fostering creativity. This article examines the importance of interactive methods in organizing pottery lessons. Interactive methods such as hands-on demonstrations, collaborative projects, and digital tools are explored for their effectiveness in engaging students and increasing their understanding of pottery techniques and traditions. The article also discusses the benefits of incorporating interactive elements into pottery education and provides insights into how teachers can optimize these methods to create dynamic and enriching learning experiences.
Keywords: Pottery education; interactive methods; hands-on demonstrations